Prevalence of anisometropia and associated factors in Shandong school-aged children - Xu, Zihang; Wu, Ziyun; Wen, Ying; Ding, Meihua; Sun, Wei; Wang, Yirong; Shao, Zhen; Liu, Yi; Yu, Mingkun; Liu, Guoyong; Hu, Yuanyuan; Bi, Hongsheng (Frontiers in Public Health, 2022)
Objective To investigate anisometropia's prevalence and associated factors in school-aged children. Methods A cross-sectional school-based study was conducted in Shandong Province, China, including children aged 4 to 17 from 9 schools. Anisometropia was defined as the differences between the two eyes in spherical equivalent (SE) or cylinder degree of 1.00 diopter (D) or more [SE or cylindrical (CYL) difference ≥ 1.00 D] after cycloplegic autorefraction. The Generalized Linear Model (GLM) was used to analyze the effects of ocular parameters [the differences between eyes in axial length (AL), habitual visual acuity (HVA), and corneal astigmatism (CA)] and lifestyle parameters (time spent indoor near work and outdoor activities) on anisometropia. Results Total 4,198 (93.4%) of the 4,494 children were included in the statistical analysis. The mean difference in inter-eye SE was 0.42 ± 0.61 D. The prevalence of anisometropia was 13.2% (95%CI: 12.1 to 14.2%) (SE anisometropia's prevalence:10.3%; CYL anisometropia's prevalence: 4.1%), increased with older age (OR = 1.10, P = 0.002), the worse myopic eye (myopia vs. premyopia, OR = 1.87, P = 0.002), the worse hyperopic eye (hyperopia vs. premyopia, OR = 1.77, P = 0.013), larger difference in inter-eye AL (0.1–0.3 vs. ≤ 0.1, OR = 1.67, P = 0.008; >0.3 vs. ≤ 0.1, OR = 28.61, P < 0.001), HVA (>0.2 vs. ≤ 0.2, OR = 3.01, P < 0.001), CA (OR = 6.24, P < 0.001), the worse stereoacuity (>100 vs. ≤ 100, OR = 1.59, P = 0.001), longer indoor near work time per day on weekends (4–8 vs. <4, OR = 1.41, P = 0.038; ≥8 vs. <4, OR = 1.40, P = 0.131), and shorter outdoor activity time per day on weekdays (≥1 vs. <1, OR = 0.75, P = 0.046) in multivariable analysis. In the SE anisometropia group, the difference in inter-eye AL (>0.3 vs. ≤ 0.1, β: 0.556, 95%CI: 0.050 to 1.063), HVA (>0.2 vs. ≤ 0.2, β: 0.511, 95%CI: 0.312 to 0.710), and CA (β: 0.488, 95%CI: 0.289 to 0.688), stereoacuity (>100 vs. ≤ 100, β: 0.299, 95%CI: 0.110 to 0.488) had a positive impact on the difference in inter-eye SE. Conclusions Ocular parameters and lifestyle parameters are associated with the occurrence of anisometropia in children aged 4 to 17 years, including the difference in inter-eye AL, HVA, CA, stereoacuity, indoor near work time, and outdoor activity time. Preventing myopia and early treating anisometropic amblyopia may be effective ways to reduce the prevalence of anisometropia.